TINJAUAN YURIDIS KETERSEDIAAN RUANG TERBUKA HIJAU PUBLIK DI KOTA PEKANBARU: Title Legal Review of the Availability of Public Green Open Spaces in the City of Pekanbaru - Ryzkya Amanda Putri; Meta Indah Budhianti (Faculty of Law, Universitas Trisakti, 2024)
The availability of green open space (RTH) is an obligation that must be fulfilled by every region, namely 30% as stipulated in the Spatial Planning Law. Regarding this RTH, it turns out that it does not correspond to the reality in the city of Pekanbaru. Therefore, this research will analyze two main problems. First, whether the availability of RTH in the city of Pekanbaru has complied with the Spatial Planning Law. Second, what are the constraints in fulfilling the availability of RTH and what efforts have been made by the Pekanbaru City Government to overcome these constraints. This research applies normative legal research methods. The results of this study reveal that Pekanbaru City has not met the 30% availability of green open space (RTH), facing obstacles such as limited land, budget constraints, and high land prices. Efforts that can be made by the Pekanbaru City Government include collaborating with investors and the private sector. In conclusion, Pekanbaru City has not met the RTH availability standards set by law due to these challenges. Collaboration with investors and the private sector is expected to address this issue and enhance RTH for the welfare of the environment and the community.